Flow structure in front of the broad-crested weir - Zachoval, Zbyněk; Roušar, Ladislav (EDP Sciences, 2014)
The paper deals with research focused on description of flow structure in front of broad-crested weir. Based on experimental measurement, the flow structure in front of the weir (the recirculation zone of flow and tornado vortices) and flow structure on the weir crest has been described. The determined flow character has been simulated using numerical model and based on comparing results the suitable model of turbulence has been recommended.

The paper deals with research focused on description of flow structure in front of broad-crested weir. Based on experimental measurement, the flow structure in front of the weir (the recirculation zone of flow and tornado vortices) and flow structure on the weir crest has been described. The determined flow character has been simulated using numerical model and based on comparing results the suitable model of turbulence has been recommended.
Flow structure in front of the broad-crested weir
Keywords: broad-crested weir; numerical model; recirculation zone; broad-crested weir; numerical model; recirculation zone